Upaya Meningkatkan Prestasi Belajar IPA melalui Model Pembelajaran Kooperatif Tipe Group Investigation di MIN 5 Gunungkidul - Faiqotul Asriyah (Pusat Pengembangan Madrasah (PPM), dan Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2021)
This research aims to find out the improvement of IPA subject learning achievement through a Group Investigation type cooperative learning model. The study was conducted at MIN 5 Gunungkidul with the research subjects of students of class VI of the 2017/2018 School Year. The study uses class action methods including planning, execution, observation, test and documentation activities. The results showed the use of the Group Investigation model can improve IPA learning achievement as evidenced by the average grade in the student class in pre-cycle activities of 69.47 with learning completion of 46.67% with sufficient criteria increased to 74.93 with learning completion by 60% including high criteria in cycle I, and increased to 84.93 with 86.67% learning completion including very high criteria in cycle II. The Group Investigation model can be applied to students at MIN 5 Gunungkidul.